2012
DOI: 10.1111/j.1440-1797.2012.01657.x
|View full text |Cite
|
Sign up to set email alerts
|

Low molecular weight heparin decreases the permeability of glomerular endothelial cells when exposed to pre‐eclampsia serum in vitro

Abstract: Low molecular weight heparin maintains the integrity of the kidney probably by strengthening the defence of glomerular endothelium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Glomerular endothelial cells exposed to serum from women with PE demonstrate an increase in permeability and endothelin-1 mRNA expression; both the permeability of these cells and endothelin-1 expression were decreased in the presence of LMWH. 65 These results indicate that LMWH is able to restore the glomerular endothelial cell function disrupted by maternal PE serum. Additional rat models with inhibited endothelial NO synthase function demonstrated that LMWH was able to reduce proteinuria, lower blood pressure, and protect overall renal function.…”
Section: Does Lmwh Improve Vascular Function?mentioning
confidence: 78%
“…Glomerular endothelial cells exposed to serum from women with PE demonstrate an increase in permeability and endothelin-1 mRNA expression; both the permeability of these cells and endothelin-1 expression were decreased in the presence of LMWH. 65 These results indicate that LMWH is able to restore the glomerular endothelial cell function disrupted by maternal PE serum. Additional rat models with inhibited endothelial NO synthase function demonstrated that LMWH was able to reduce proteinuria, lower blood pressure, and protect overall renal function.…”
Section: Does Lmwh Improve Vascular Function?mentioning
confidence: 78%
“…Cells were removed from the culture bottles after 6 and 12 h and treated as follows: (i) The cells were washed twice with DMEM containing 1% FBS; (ii) the cells were digested with 0.5% trypsin and placed into a flow cytometry detection tube; (iii) the cell suspension was centrifuged at 1,847 × g for 10 min and the supernatant was discarded; (iv) the precipitate was washed twice with phosphate-buffered saline (PBS) and centrifuged at 462 × g for 5 min to isolate the cells; (v) the cells were fixed with 4% paraformaldehyde for 10 min at 4°C and 30 min at room temperature and the samples were then centrifuged at 462 × g for 5 min to remove the supernatant; (vi) the cells were washed twice with PBS and centrifuged at 462 × g for 5 min to discard the liquid; (vii) 1 ml of 0.5mg/l FITC-phalloidin (100 μ g FITC-phalloidin was dissolved in 0.2 ml methanol and diluted with 0.01 M PBS) was added, and the cells were reacted for 40 min in the dark; (viii) samples were washed with PBS three times and centrifuged at 462 × g for 5 min to remove the supernatant and eliminate the uncombined FITC-phalloidin; and (ix) cells were gently blended after adding 0.8 ml PBS. The changes in F-actin were detected by flow cytometry (FACScalibur™; BD Biosciences, Franklin Lakes, NJ, USA), with the absence of FITC-phalloidin in the negative control group (16,17). …”
Section: Methodsmentioning
confidence: 99%
“…GENCs were inoculated on the membrane at a density of 5×10 5 /per hole. The membrane was removed from the nesting after 7–10 days, based on previous studies (17,18), which showed that ECs reach a state of cell fusion and covered the filter membrane within a period of 7–10 days. The membrane was then washed three times with PBS, fixed with 95% alcohol for 10 min, washed again three times with PBS, stained with hematoxylin and eosin for 5 min and rinsed with water three times.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation